Scalable asynchronous localization algorithm with mobility prediction for underwater wireless sensor networks. (February 2021) - Dong, Mingru; Li, Haibin; Yin, Rongrong; Qin, Yuhua; Hu, Yongtao
Abstract: With the exploration of ocean resources, underwater wireless sensor networks have become a new research focus. Localization is one of most important technologies in the application of underwater wireless sensor networks. Because of the complex of underwater environment, it is difficult to realize the precisely synchronous localization in the underwater wireless sensor networks especially the large-scale networks with mobility. To solve this problem, in this paper, we propose a scalable asynchronous localization algorithm with mobility prediction. In this localization algorithm, the large-scale underwater wireless sensor network architecture is designed. Considering the node mobility, the node motion model is built based on the tidal mobility. By analyzing the asynchronous communication between the anchor nodes and ordinary nodes, the initial position of ordinary nodes is obtained and the future position of ordinary nodes is predicted and updated. The precisely located ordinary nodes are upgraded to new reference nodes and the new reference nodes locate the other unknown ordinary nodes together with the anchor nodes until the localization tasks of all ordinary nodes are completed. Simulation results confirm that the proposed localization algorithm can achieve accurate localization of mobile nodes in large-scale underwater wireless sensor networks with asynchronous clock.